2016
DOI: 10.1111/gcb.13155
|View full text |Cite
|
Sign up to set email alerts
|

Integrating theory into disturbance interaction experiments to better inform ecosystem management

Abstract: Managing multiple, interacting disturbances is a key challenge to biodiversity conservation, and one that will only increase as global change drivers continue to alter disturbance regimes. Theoretical studies have highlighted the importance of a mechanistic understanding of stressor interactions for improving the prediction and management of interactive effects. However, many conservation studies are not designed or interpreted in the context of theory and instead focus on case-specific management questions. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
72
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 83 publications
(73 citation statements)
references
References 59 publications
0
72
0
1
Order By: Relevance
“…; Foster et al . ). As an example, altered (and intensive) herbivore grazing regimes interact with fire regimes in Australian coastal forests and have considerably greater negative effects on vegetation than either of these in isolation (Foster et al .…”
Section: What Could Managers Do To Limit the Risks Of Forest Ecosystementioning
confidence: 97%
See 1 more Smart Citation
“…; Foster et al . ). As an example, altered (and intensive) herbivore grazing regimes interact with fire regimes in Australian coastal forests and have considerably greater negative effects on vegetation than either of these in isolation (Foster et al .…”
Section: What Could Managers Do To Limit the Risks Of Forest Ecosystementioning
confidence: 97%
“…Foster et al . () provided a valuable experimental framework for studies to help distinguish the potential impacts of multiple interacting stressors, including how to underpin such studies with relevant ecological theory (Figure ). Notably, many investigations have demonstrated that the demise of individual species stems from multiple interacting factors (eg Woinarski et al .…”
Section: What Could Managers Do To Limit the Risks Of Forest Ecosystementioning
confidence: 99%
“…Given increasing anthropogenic pressures (e.g., land use changes, human population growth, species introductions) and climate change, increased disturbance frequency, as well as interactions among disturbances, are likely consequences in the future (Seidl et al 2014, Buma 2015, Foster et al 2016. Although a relatively small proportion of fires have occurred in beetle-killed fuels in the western US over the last three decades (0.5 % to 1.3 %), there are recent examples of fires burning through forests with high levels of beetle-impacted fuels .…”
Section: Discussionmentioning
confidence: 99%
“…As outlined above, adequate replication of large experimental units (such as entire landscapes) for true experiments is often difficult, and it is even more of a challenge when the target species for study are wide-ranging, highly mobile taxa, such as birds and bats [27]. In other cases, the strict statistical design constraints that underpin true experiments may limit the kinds of potentially important factors and/or management interventions that can be tested, including complex interactions among factors (but see [28]). For example, the Suitability of Altered Forest Ecosystems Project (SAFE) in Borneo is quantifying a range of drivers of effects of fragmentation, but the effects of matrix conditions surrounding fragments are not being examined despite their importance being increasingly recognised [29].…”
Section: True Experimentsmentioning
confidence: 99%